2021
DOI: 10.1007/s00330-020-07586-y
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery lumen volume index as a marker of flow-limiting atherosclerosis—validation against 13N-ammonia positron emission tomography

Abstract: Objectives Coronary artery volume indexed to left myocardial mass (CAVi), derived from coronary computed tomography angiography (CCTA), has been proposed as an indicator of diffuse atherosclerosis. We investigated the association of CAVi with quantitative flow parameters and its ability to predict ischemia as derived from 13N-ammonia positron emission tomography myocardial perfusion imaging (PET-MPI). Methods Sixty patients who underwent hybrid CCTA/PET-MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Such a result supports the idea of a normalization of atheroma burden to the volume of the coronary arterial tree. Moreover, the same research group demonstrated that CAVi is independently associated with abnormal stress myocardial blood flow (MBF), as derived from 13 N-ammonia positron emission tomography myocardial perfusion imaging [ 39 ]. More importantly, CAVi exhibits incremental value to predict abnormal MBF and ischemia over stenosis severity from CCTA alone.…”
Section: Association Of Coronary Geometry With Atherosclerosis Lesion...mentioning
confidence: 99%
“…Such a result supports the idea of a normalization of atheroma burden to the volume of the coronary arterial tree. Moreover, the same research group demonstrated that CAVi is independently associated with abnormal stress myocardial blood flow (MBF), as derived from 13 N-ammonia positron emission tomography myocardial perfusion imaging [ 39 ]. More importantly, CAVi exhibits incremental value to predict abnormal MBF and ischemia over stenosis severity from CCTA alone.…”
Section: Association Of Coronary Geometry With Atherosclerosis Lesion...mentioning
confidence: 99%
“…The study intends to recruit 100 consecutive patients with suspected CAD and low/intermediate pre-test probability. Coronary geometrical characteristics such as angulation of coronary bifurcations, tortuosity, coronary artery volume index [38] and vessel-length will be assessed with multi-planar reformation and volume rendering techniques (Figure 2) and integrated into a single geometric risk score. The extent and vulnerability of plaque burden will be calculated using several anatomical scoring systems such as the Leiden CTA risk score [39] and CT-adapted Gensini score [40].…”
Section: Association Of Coronary Geometry With Atherosclerosis Lesion...mentioning
confidence: 99%